Quantifying the burden of hereditary hemorrhagic telangiectasia on quality of life and psychological health: a cross-sectional study - Anna J. Gong; Marisabel Linares Bolsegui; Emerson E. Lee; Matthew R. Tan; Yong Zeng; Jianqiao Ma; Prateek C. Gowda; Tushar Garg; Clifford R. Weiss (Orphanet Journal of Rare Diseases)
Abstract Background Despite the considerable burden that hereditary hemorrhagic telangiectasia (HHT) imposes, few studies have investigated its effect on health-related quality of life (HRQoL). We aimed to assess the impact of HHT on psychosocial QoL and identify demographic and clinical factors associated with lower QoL. Methods We conducted an international, cross-sectional study of 1042 adults with HHT within the Cure HHT network, between 2022 and 2023. We used an online survey that included 5 standardized instruments to evaluate patients’ perceptions of the impact of HHT on their QoL: Epistaxis Severity Score (ESS); Nasal Outcome Score for Epistaxis in Hereditary Hemorrhagic Telangiectasia (NOSE-HHT); Patient-Reported Outcomes Measurement Information System (PROMIS) Fatigue – Short Form 8a – Fatigue interfere scale (PROMIS-Fatigue 8a); Hospital Anxiety and Depression Scale (HADS-A and HADS-D); and Short Form Health Survey (SF-36). Statistical analyses included Spearman’s correlations, univariate analyses, Tukey’s honestly significant difference, and Kruskal-Wallis tests. Results 565/1042 (54%) participants completed the survey. The most common symptoms were epistaxis 521/565 (92%) and fatigue 446/565 (79%). There were strong positive correlations between HADS-A and ESS (2.6 [95% CI 1.7–3.6]) and NOSE-HHT (4 [3.2-5]); HADS-D and ESS (1.4 [1.3–1.5]) and NOSE-HHT (4.4 [3.4–5.7]); PROMIS Fatigue 8a and ESS (8.2 [6.3–10]) and NOSE-HHT (5.9 [5.2–6.6]); and SF-36 scores and ESS (− 26.4 [− 33 to − 19.9]) and NOSE-HHT (− 33.1 [− 39.7 to − 28.6]). Liver failure and seizures indicated a higher likelihood of depression (3.1 [1-5.2]), anxiety (3 [0.6–5.4]), and fatigue (9.6 [4.7–14.5]). Seizures were associated with depression (2.9 [1.8–3.9]), anxiety (2.9 [1.7–4.1]), and fatigue (5 [2.34–7.7]). Participants expressed a substantial effect on their physical (143/560 [25%]), role (140/556 [25%]), emotional (124/554 [22%]), social (104/556 [18%]), and cognitive (64/550 [11%]) functioning. However, more participants considered extremely important to improve their physical (289/560 [51%]), cognitive (266/550 [47%]), role (253/556 [43%]), emotional (243/554 [45%]), and social (233/556 [41%]) functioning affected by HHT. Conclusions Severe epistaxis is associated with higher rates of depression, anxiety, and fatigue. Participants expressed desire for improvement in a broad range of functional domains disturbed by HHT. This suggests a need for increased awareness, resources, and more effective interventions to improve the QOL of patients with HHT.